Analysis of Polygamy Practices in Batak Muslim Community in South Rantau Based on Law No. 16 of 2019 about Marriage and Islamic Law - Nazwah Nazwah (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2022)
The Batak Muslim community in South Rantau considers marriage as a means to produce offspring to continue the male kinship side, in this case, the clan. So, if a marriage does not give birth to a son, the clan lineage is considered broken and cannot continue the clan lineage and inheritance. And also, if the marriage is still to be maintained, a husband can perform presidia-duo (two wives). The practice of polygamy in the South Rantau sub-district is carried out due to biological and economic conditions. The people who practice polygamy a lot are the Batak Muslim community. This situation creates a dilemma between obedience to religion and adherence to the law. On religious observance, they rely on the practice of polygamy based on understanding the QS. An-Nisa: 3. Meanwhile, compliance with the law is based on the Law of the Republic of Indonesia Number 16 of 2019 concerning marriage amendments to the Law of the Republic of Indonesia Number 1 of 1974. From here, this study discusses the practice of polygamy in the South Batak Rantau Muslim community, with reference to the provisions of Islamic law and Undang-undang. This research is field research by conducting observations, interviews, and documentation in the District of South Rantau. From here, the formulation of the problem to be answered in this study is how the practice of polygamy carried out by the Muslim community is understood through Law No. 16 of 2019 and Islamic Law.